(3CfhGQ GdYbhd ef CTYGQ hUj GdQShds - (3GdfjSGHhQj, GdcjOQj, CHh GdMSf, bWH GdOjf, eMeO Hf GdMSjf Hf GdMSf, J (B576 (3g`s
(3ChdgG (B:s
(3bGd CejQ GdeDefjf Ydj Hf CHj WGdH (B... (3GdfGS ef LgI GdJeKGd CcaGA (B*** (3CHhge BOe hGdCe MhGAs
(3BNQgG (B:s
(3JhSd HGdfHj acd NWH(B***(3jRhd EPG JhSd HGdfHj, JhSd EPG eG fGH NWH(B***(3hce ddg ef dWa Najs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf(B:(3L(B3(3,U(B248s
(3GdPQjYI(B:(3L(B2(3,U(B241(3,b(B1697s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdCOHs